Teaching and Learning About Communities : Principles and Practices - Kravetz, Katharine (Palgrave Macmillan US : Imprint: Palgrave Pivot, 2017)
This book provides a rationale and conceptual framework for teaching and learning about community. It focuses on what community means in multiple contexts, outlines the needs and assets of communities, and discusses different approaches to community change. The book provides real life examples of integrated approaches to community transformation as well as sample exercises to promote a better understanding of community challenges and approaches to solve them. Applicable in the classroom and in actual community work, the book's conceptual and practical approach can be used to study community, or to integrate community issues into learning in virtually any field. Katharine Kravetz is Assistant Professor Emerita in the School of Professional and Extended Studies at American University, USA. She founded and taught American University's Washington Semester Transforming Communities and Public Policy Seminar. Kravetz has received the Harvard/Radcliffe Undergraduate History Prize and the Adjunct Faculty Teaching Award from American University's School of Public Affairs.- Resumé vydavatel